The design modification of advanced ventricular assist device to enhance pulse augmentation and regurgitant flow shut‐off. Issue 10 (18th June 2019) - Miyamoto, Takuma; Byram, Nicole; Karimov, Jamshid H.; Adams, Joseph; Dessoffy, Raymond; Kuban, Barry D.; Gao, Shengqiang; Horvath, David J.; Fukamachi, Kiyotaka
Abstract: The new Advanced ventricular assist device (Advanced VAD) has many features such as improving pulsatility and preventing regurgitant flow during pump stoppage. The purpose of this study was to evaluate the effects of design modifications of the Advanced VAD on these features in vitro. Bench testing of four versions of the Advanced VAD was performed on a static or pulsatile mock loop with a pneumatic device. After pump performance was evaluated, each pump was run at 3000 rpm to evaluate pulse augmentation, then was stopped to assess regurgitant flow through the pump. There was no significant difference in pump performance between the pump models. The average pulse pressure in the pulsatile mock loop was 23.0, 34.0, 39.3, 33.8, and 37.3 mm Hg without pump, with AV010, AV020 3S, AV020 6S, and AV020 RC, respectively. The pulse augmentation factor was 48%, 71%, 47%, and 62% with AV010, AV020 3S, AV020 6S, and AV020 RC, respectively. In the pump stop test, regurgitant flow was −0.60 ± 0.70, −0.13 ± 0.57, −0.14 ± 0.09, and −0.18 ± 0.06 L/min in AV010, AV020 3S, AV020 6S, and AV020 RC, respectively. In conclusion, by modifying the design of the Advanced VAD, we successfully showed the improved pulsatility augmentation and regurgitant flow shut‐off features.